Effective team building in the shea butter industry – a case of Tolon district - Mohammed, Haruna (KNUST, 2025)
A thesis Submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in Partial fulfilment of the requirements for the award of the Degree of Master of Science in Project Management